2020
DOI: 10.1155/2020/8890182
|View full text |Cite
|
Sign up to set email alerts
|

Kang‐Xian Pills Inhibit Inflammatory Response and Decrease Gut Permeability to Treat Carbon Tetrachloride‐Induced Chronic Hepatic Injury through Modulating Gut Microbiota

Abstract: Kang-Xian (KX) pills have been clinically used for the treatment of chronic hepatic injury (CHI). However, the mechanisms of KX on CHI remain unknown. The aim of this study mainly focused on the anti-inflammatory effects of KX in a CHI mouse model based on modulating gut microbiota and gut permeability. We first established a CHI model using carbon tetrachloride (CCl4) and treated it with KX. The anti-inflammatory effects of KX on CHI model mice and the changes in gut permeability after KX treatment were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Meanwhile, pathological change of liver histological also demonstrated that KXP treatment significantly alleviate CCL4-induced hepatocytes extensive edema and necrosis. In addition, our previous study demonstrated that KXP could alleviate the inflammation response of CCL4-induced CHI by regulating gut microbiota 7 . However, as an empirical formula, KXP consists of 12 Chinese medicines and contains multi-compounds, and it's tough to clarify the multi-molecular mechanisms with conventional experimental methods.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, pathological change of liver histological also demonstrated that KXP treatment significantly alleviate CCL4-induced hepatocytes extensive edema and necrosis. In addition, our previous study demonstrated that KXP could alleviate the inflammation response of CCL4-induced CHI by regulating gut microbiota 7 . However, as an empirical formula, KXP consists of 12 Chinese medicines and contains multi-compounds, and it's tough to clarify the multi-molecular mechanisms with conventional experimental methods.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous study showed that KXP exerted hepatic protective effect through decreasing levels of transaminase and raising activities of superoxide dismutase (SOD) and increasing contents of and glycogen (Gn) 6 . In addition, KXP could alleviate chronic liver injury through regulating gut microbiota to inhibit permeability of intestinal epithelial 7 . However, major hepatoprotective targets of KXP remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…We established a liver fibrosis mouse model via intraperitoneal injection of CCl 4 , which was consistent with previous study (Wang et al, 2020). Briefly, CCl 4 was diluted with olive oil at a concentration of 2 ml/kg body weight and administered via intraperitoneal infusion twice per week over a six-week period.…”
Section: Induction Of Liver Fibrosis Mouse Modelmentioning
confidence: 92%
“…We followed the methods of Wang et al 2020 [ 18 ]. Total RNAs were isolated from livers using the RNA extraction kit, and first-strand cDNAs were synthesized from 1 μ g of total RNAs according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…We followed the methods of Wang et al 2020 [ 18 ]. Briefly, rat colons were removed and fixed in paraffin, and the expression of occludin and tight junction protein-1 (ZO-1) in the colon was accessed via immunostaining.…”
Section: Methodsmentioning
confidence: 99%